Pengaruh Pengeluaran Pemerintah, Pengangguran dan Pertumbuhan Ekonomi terhadap Tingkat Kemiskinan di Provinsi Kalimantan Selatan - Khamilah, Henny (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
This study entitled "The Effect of Government Expenditure, Unemploymentand Economic Growth on Poverty Rate in South Kalimantan Province."The purpose of this research is to know the effect of GovernmentExpenditure, Unemployment Rate, and Economic Growth on the Poverty Level inSouth Kalimantan Province.The method of analysis used is multiple linear regression time-series data ofthis research using observation of 11 years from 2006 until 2016 existing dataprocessed by using the tool of computer program E-views 9.0.Based on the result of the research, the development of governmentexpenditure has the positive and insignificant influence to the poverty rate in SouthKalimantan Province; unemployment has a positive and significant effect to thepoverty level in South Kalimantan Province, economic growth has a negative andinsignificant impact on poverty level in South Kalimantan Province.